The Association between Benefits Realization and Dubai/UAE Infrastructure Development Projects Outcomes - ALSHARIF, AHMAD ABDULRAHMAN (2018)
Purpose: The objective of this research was to assess association between benefits realization and Dubai/UAE infrastructure development projects outcomes. Design: To conduct this research, a questionnaire was compiled and distributed to the respondents to collect the data. The objective of the researcher was to formulate the questionnaire quickly and accurately. In addition, a brief test guaranteed the comfort of the participants and the feeling of being at ease. In terms of research segmentation, this included an ethics section and three main sections. The first part of the questionnaire was based on the demographic data of the interviewees. The second section of the questionnaire contained questions about the factors that influence the independent variable, totaling 25 questions. The third part of the questionnaire also raised questions about the factors that influenced the dependent variables of the project (performance) and a similar number of 25 questions. Findings: The results of the research provided that there is significant positive relationship between Benefits Realization and UAE Infrastructure development project outcomes along with a significant positive relationship between UAE Infrastructure development project outcomes and Identifying Benefits. Moreover, the study also identified significant positive relationship between UAE Infrastructure development project outcomes and Executing benefits Research limitations: The main focus of the research was only towards association between benefits realization and infrastructure development projects outcomes in Dubai/UAE Furthermore, for the purpose of collecting data, only survey questionnaires were being utilized. Practical Implications: The research revealed a number of individuals who have reviewed the issue of benefits realization. Among them is Levin (2015) who considers benefits to be a critical part in the project cycle. The study reflected upon the complexities surrounding projects imply that team and stakeholders identify the benefits as a key part of organizational projects. The emphasis on benefits necessitates the identification of the gains from a program Originality: With respect to association between benefits realization and Dubai/UAE infrastructure development projects outcomes, this study is based on existing research and literature.